Role of Placenta Location and Uterine Artery Doppler Assessment at 18 To 24 Weeks as Predictors of Pre-Eclampsia - Navkiran Kaur; Piyush Singh; Parneet Kaur (Asian Journal of Medical Radiological Research, 2020)
Background: Preeclampsia, a pregnancy disorder, is defined as a systemic syndrome characterized by new-onset of hypertension and proteinuria after 20 weeks of gestational age in pregnant women, which resolves before the end of 6th week postpartum. Hence; under the light of above mentioned data, we planned the present study to establish the role of placenta location and uterine artery doppler assessment at 18 to 24 weeks as predictors of pre-eclampsia. Subjects and Methods: First 100 patients were scanned at 18-24 weeks and were followed up till delivery. The location of the placenta and uterine artery Doppler was determined by ultrasound using Phillips HD11 XE ultrasound machine with a 3.5-MHz curvilinear transducer at 18-24 weeks in all the cases at the time of scan. The end point of the study was the development of preeclampsia. The study group included 100 patients reporting to ultrasound section. Grey scale ultrasound and colour doppler was performed. Any co-relation of radiological findings with clinical and surgical findings were documented and analysed. Results: Significant results were obtained while assessing distribution of patients in relation to lateral placenta location, Doppler study and occurrence of pre-eclampsia. 87 percent of the patients had central located placenta while in the remaining 13 percent of the patients had lateral located placenta. While assessing the 100 patients, we observed that Pre-Eclampsia was found to be present in 12 percent of the patient. Conclusion: By identifying the high risk patients & anticipating preeclampsia patients can be monitored more closely to reduce the morbidity and improve the outcome of pregnancy.